Evaluasi Program Fit To Work Terhadap Upaya Peningkatan Produktivitas Kerja Operator Di PT Pelindo Terminal Petikemas - Ula, Wahyu Khiarotul; Andi Sani; Nurul Hikmah B (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Fit to work is a health check given to workers with the aim of determining the physical abilities of workers so that they are able to carry out their work properly. PT Pelindo Terminal Petikemas New Makassar Terminal 2 has implemented a health check through a fit-to-work program that is carried out every day. This program requires all operators to undergo a health check before starting their shift, ensuring that they are fit and healthy to perform their duties. The study aimed to evaluate the fit-to-work program towards increasing operator work productivity at PT Pelindo Terminal Petikemas New Makassar Terminal 2. The type of research used qualitative research with a descriptive approach. The informants of this study were Duty Planner, HSSE Staff, Health Officers and Operators at PT Pelindo Terminal Petikemas New Makassar Terminal 2. The selection of informants was carried out by applying data collection methods based on special considerations, such as the expertise of informants in the subjects studied or having the highest position in the relevant agency, so that it can help researchers gain deeper insight into the object or situation being studied. From the results of the study, it was obtained that health workers, health check facilities and infrastructure and worker health checks can minimize the risk of work accidents and can increase work productivity. It is expected that PT Pelindo will further improve and develop the knowledge of health workers regarding Occupational Health and Safety (K3) standards and regulations, evaluate the latest technology by reviewing and comparing various new technologies that can be applied in health examination facilities and efforts need to be made so that workers always follow the implementation of the fit to work program in order to minimize the risk of work accidents and increase work productivity.